The Refugee Health Nurse Liaison: a nurse led initiative to improve healthcare for asylum seekers and refugees. Issue 6 (28th October 2016) - McBride, Jacquie; Russo, Alana; Block, Andrew
Abstract : Asylum seekers and refugees experience a range of barriers to health service access and competent use. The Refugee Health Nurse Liaison initiative was piloted at a hospital in a high-settlement region of Victoria, Australia. This initiative aimed to build capacity within the health sector to more effectively respond to the needs of asylum seekers and refugees. A mixed-methods evaluation was undertaken to: describe issues encountered by asylum seekers and refugees within the hospital setting; capture the nature of the Refugee Health Nurse Liaison position; and document key outputs. Throughout the pilot period, 946 patients were referred to the role, of which 99% received an assessment of physical, mental, and social health. Refugee Health Nurse Liaisons effectively provided clinical support, advocacy, education, referrals, and both formal and informal capacity building. Learnings from this model are transferable to services in high-settlement regions, and could have application in improving patient care more broadly.